2021
DOI: 10.3390/md19110593
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Extraction of Polar Lipids from Nannochloropsis oceanica for Food, Feed, and Biotechnology Applications Evaluated Using Lipidomic Approaches

Abstract: Nannochloropsis oceanica can accumulate lipids and is a good source of polar lipids, which are emerging as new value-added compounds with high commercial value for the food, nutraceutical, and pharmaceutical industries. Some applications may limit the extraction solvents, such as food applications that require safe food-grade solvents, such as ethanol. However, the effect of using ethanol as an extraction solvent on the quality of the extracted polar lipidome, compared to other more traditional methods, is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 68 publications
2
20
0
Order By: Relevance
“…The lipid species identified here were consistent with those previously reported for Nannochloropsis [ 34 ]. Relative to the control, neutral lipid, glycolipid, and phospholipid levels were all lower after combined enzyme treatment ( Figure 2 ).…”
Section: Resultssupporting
confidence: 91%
“…The lipid species identified here were consistent with those previously reported for Nannochloropsis [ 34 ]. Relative to the control, neutral lipid, glycolipid, and phospholipid levels were all lower after combined enzyme treatment ( Figure 2 ).…”
Section: Resultssupporting
confidence: 91%
“…Lipidomics has also been applied to find alternative extraction procedures using food grade solvents and sustainable methodologies to obtain lipid extracts compatible with food applications. 8,91 In the case of N. oceanica and C. vulgaris the authors reported that lipid extracts obtained using ethanol and assisted with ultrasound had a lipid composition similar to those obtained using conventional methods based on Folch extraction protocol. 6,8,91 The authors of these studies suggested an alternative green lipid extraction method to provide safe extracts for functional food applications.…”
Section: Lipidomics Of Macroalgae Microalgae and Halophytesmentioning
confidence: 95%
“…The replacement of chloroform by dichloromethane in the Bligh and Dyer method 5 or Folch method 6 was shown to give in most cases similar yields of lipid extraction and similar results in the lipidome profile as reported for the microalgae Nannochloropsis oceanica. 7,8 However, the use of different proportions of organic solvents or cell disruption methods can result in different yields of lipids. 9 Lipid extraction using MTBE:methanol is becoming popular in lipidomic analysis because the MTBE:methanol phase (the organic phase with the dissolved lipids) is in the upper phase, which makes handling much easier than with chloroform or dichloromethane.…”
Section: Lipid Extraction and Fractionationmentioning
confidence: 99%
See 2 more Smart Citations